Fault Diagnosis and Detection Based on Efficiency Loss Test of Photovoltaic Power Station. Issue 1 (May 2020) - Xie, Xiangying; Meng, Fanteng; Luo, Xin; Cai, Shixia; Ma, Xiaoguang; Na, Zhixiong; Ma, Dayan; Shan, Yu; Ge, Leyi; Liu, Yunchao
Abstract: The existing operation and maintenance system of photovoltaic power station can analyze partial equipment problems, but due to the data storage, processing and transmission capacity can hardly meet the requirements of a large number of operation data acquisitions and processing of photovoltaic power station, the operation status of photovoltaic power station cannot be comprehensively evaluated. This paper proposes to analyze the overall efficiency and key link efficiency of the photovoltaic system through long-term monitoring, extract the efficiency model parameters of the key components and important links of the photovoltaic power station, and establish the performance evaluation implementation process. At the same time, based on different actual detection conditions, photovoltaic fault diagnosis is carried out by time domain reflectometry, prediction theory comparison and sensor optimization.